Estudo do valor nutritivo do "ora-pro-nobis" (Pereskia aculeata Mill) - de Almeida Filho, José; Cambraia, José (Revista Ceres, 2025)
"Ora-pro-nobis"(Pereskta aculeata Mill) leaves were analized to determine the extent they could be considered as a protein source for animal feeding and human consumption. Protein contents in samples from two locations were 17.4% and 25.5% with a mean digestibility of 85.0%. Lysine contents in two samples, 5.43 and 5.42 g/100 g protein, were high as compared to those found in leaves of species such as lettuce, cabbage and spinach, with high water content. The same was found with respect to calcium, phosphorus and magnesium in the ash fraction.